STATORS USE INFLUENCE ON THE PERFORMANCE OF A SAVONIUS WIND ROTOR USING COMPUTATIONAL FLUID DYNAMICS - Akwa, J. V.; Petry, A. P. (Revista de Engenharia Térmica, 2011)
This paper aims at verifying the influence of using five kinds of stators in the averaged moment and power coefficients of a Savonius wind rotor using computational fluid dynamics (CFD). The analyzed stators have cylindrical shape with two and three openings, one and four deflector blades and walls shaped like a wings. The equations of continuity, Reynolds Averaged Navier-Stokes – RANS and the Eddy Viscosity Model k-ω SST, in its Low-Reynolds approaches, with hybrid near wall treatment; are numerically solved using the commercial software Star-CCM+, based on Finite Volume Method, resulting in the fields of pressure and velocity of the flow and the forces acting on the rotor buckets. The moment and power coefficients are achieved through integration of forces coming from the effects of pressure and viscosity of the wind on the buckets device. The influence of the stators use in the moment and power coefficients is checked by changing the geometry of the device for each simulations series, keeping the Reynolds number based on rotor diameter equal to 433,500. The obtained values for averaged moment and power coefficients indicate that for each type of stator used, there was maximum performance for a given tip speed ratio of rotor. Improvement in performance over the operation without stator was obtained only to the operations using stator with four deflector blades and to the stator with cylindrical shape with three openings. The improvement percentage in performance obtained for the best condition (use of four deflector blades at tip speed ratio equal to 1) is 12% compared to the performance of the rotor operating without stator.